2017
DOI: 10.1515/afe-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

ATD and DSC Analysis of IN-713C and ZhS6U-VI Superalloys

Abstract: Paper presents the results of ATD and DSC analysis of two superalloys used in casting of aircraft engine parts. The main aim of the research was to obtain the solidification parameters, especially Tsol and Tliq, knowledge of which is important for proper selection of casting and heat treatment parameters. Assessment of the metallurgical quality (presence of impurities) of the feed ingots is also a very important step in production of castings. It was found that some of the feed ingots delivered by the superall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The solidus temperatures were also compared with those measured for cast irons. In this case, the average deviation for 52 alloys from other studies [50,51,[117][118][119][120][121][122][123][124][125][126] was 6.6 °C. Note that these measurements may have been related also to the eutectic temperature, due to the difficulty of distinguishing the corresponding DTA information of solidus from the eutectic.…”
Section: Solidus Temperaturementioning
confidence: 65%
See 1 more Smart Citation
“…The solidus temperatures were also compared with those measured for cast irons. In this case, the average deviation for 52 alloys from other studies [50,51,[117][118][119][120][121][122][123][124][125][126] was 6.6 °C. Note that these measurements may have been related also to the eutectic temperature, due to the difficulty of distinguishing the corresponding DTA information of solidus from the eutectic.…”
Section: Solidus Temperaturementioning
confidence: 65%
“…The liquidus temperatures were also compared with those measured experimentally for cast irons. In this case, the average deviation for 57 alloys taken from other studies [50,51,94,[117][118][119][120][121][122][123][124][125][126] was 7.5 °C.…”
Section: Liquidus Temperaturementioning
confidence: 83%
“…Segregation within the sample can cause the solidus to be lower than it should be. The solidus of steel has also been found to be strongly dependent on cooling rate [5,6]. The peritectic reaction itself presents more difficulties in DSC due to the low energy associated with it [5].…”
Section: 𝐿 + 𝛿 ⟶ 𝛾 (1)mentioning
confidence: 99%
“…It has been widely reported that the additively manufactured Ni-based metal matrix composites (MMC) can achieve partial CET with the presence of various ceramic particles. [25][26][27][28][29][30][31][32] Among these candidates, CoAl 2 O 4 is believed to be capable of triggering grain refinement in Ni-base superalloys by interacting with reactive elements such as Cr, Ti, and Nb in the melt pool and forming elemental Co. [33,34] Previous studies have shown that a subtle addition of CoAl 2 O 4 (e.g., 0.2 wt pct) contributes to refining the grain size and reducing the degree of elastic anisotropy within L-PBF processed Alloy 718 when optimized scan parameters and 67 degree of scan rotation were applied. [35,36] The resulting oxides distributed with the microstructure were also found to impede the movement of grain boundaries during heat treatment.…”
Section: Introductionmentioning
confidence: 99%